2014
DOI: 10.1021/jp5022278
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Magnetic Field Induced Fast Drug Release from Magneto Liposomes via Ultrasound Generation

Abstract: Fast drug delivery is very important to utilize drug molecules that are short-lived under physiological conditions. Techniques that can release model molecules under physiological conditions could play an important role to discover the pharmacokinetics of short-lived substances in the body. Here an experimental method is developed for the fast release of the liposomes' payload without a significant increase in (local) temperatures. This goal is achieved by using short magnetic pulses to disrupt the lipid bilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 26 publications
2
37
1
Order By: Relevance
“…As an alternative, short magnetic pulses have been applied to rapidly release cargo from DPPC:DSPC:Chol (88:1:10) MLs, incorporating iron oxide nanoparticles. 306 This work also revealed that the magnetic nanoparticles generated US played a role in the content release from the MLs. Lately, MLs capable of encapsulating hydrophilic and lipophilic drugs have been prepared with a lipid bilayer embedded with a hydrophobic magnetite coated with oleic acid.…”
Section: Trigger-based Targetingmentioning
confidence: 65%
“…As an alternative, short magnetic pulses have been applied to rapidly release cargo from DPPC:DSPC:Chol (88:1:10) MLs, incorporating iron oxide nanoparticles. 306 This work also revealed that the magnetic nanoparticles generated US played a role in the content release from the MLs. Lately, MLs capable of encapsulating hydrophilic and lipophilic drugs have been prepared with a lipid bilayer embedded with a hydrophobic magnetite coated with oleic acid.…”
Section: Trigger-based Targetingmentioning
confidence: 65%
“…15,16 There has been interest in developing liposomes that effectively encapsulate anti-cancer agents and release them specifically within tumors. To this end, many liposome triggered-release strategies have been developed including activation methods based on pH 1720 , heat 13,21,22 , enzymes 23,24 , light 3,25,26 and magnetic pulses 27 and thermosensitive liposomes have entered clinical testing for multiple cancer indications. 28 …”
mentioning
confidence: 99%
“…Proof of concept lies in the release of molecules, such as MgSO4 and 5(6)-carboxyfluorescein, being accomplished from magneto liposomes loaded with Fe3O4 or FePt nanoparticles, both in homogeneous and inhomogeneous magnetic fields [101].…”
Section: Mechanical Action On Biostructuresmentioning
confidence: 99%